Bose-einstein condensation of two-dimensional polaritons in microcavity under the influence of the landau quantization and rashba spin-orbit coupling - Moscalenco, Vsevolod; Dumanov, Evgheni; Podlesnîi, Igor; Liberman, Michael; Novikov, Boris; Rusu, Spiridon; Bajireanu, Valentina (Moldavian Journal of the Physical Sciences, 2014)
The Bose-Einstein condensation (BEC) of the two-dimensional (2D) magnetoexcitonpolaritons in microcavity, where the Landau quantization of the electron and hole states accompanied by the Rashba spinorbit coupling plays the main role, was investigated. The Landau quantization levels of the 2D heavy holes with nonparabolic dispersion law and third-order chirality terms both induced by the external electric field perpendicular to the semiconductor quantum well and strong magnetic field B give rise to a nonmonotonous dependence of the magnetoexciton energy levels and the polariton energy branches on B.